Development and application of a priority rated optimization model (PROM) for multi-sector water resource management systems. (March 2019) - Dessu, Shimelis Behailu; Melesse, Assefa M.; Bhat, Mahadev G.; Price, Rene′ M.; Seid, Abdulkarim H.; Debebe, Senait A.; McClain, Michael E.
Abstract: We present a new Priority Rated Optimization Model (PROM) for multi-sector water resource assessment, allocation and management. PROM utilizes flow duration curves (FDC), demand-to-supply ratio (DSR) and utility indices (UI) to evaluate and optimize priority based multi-sector water allocation. DSR links demand volume and priority with corresponding supply volume and likelihood derived from segmentation of FDC. The UI function assigns weights to ranges of DSR to assess the existing and potential alternative management scenarios. Supply reliability and UI values are used in a combinatorial optimization scheme to estimate allocated volume, flow rate and percent exceedance. PROM is applied in the Mara River Basin of Kenya/Tanzania, and results showed potential improvement over the current management practice towards sustainability of the Mara-Serengeti ecosystem. PROM bridges the gap between environmental and economic models while providing a user-friendly platform for direct stakeholder involvement to explore alternative water allocation scenarios. Highlights: A new Priority Rated Optimization Model (PROM) for water resource management is developed and applied. Flow duration curves are used to estimate available water. User defined water use priorities and demand-to-supply ratios are utilized to evaluate and optimize water allocation.